2005
DOI: 10.1002/jbm.a.30366
|View full text |Cite
|
Sign up to set email alerts
|

In vitro interaction between surface‐treated Ti‐6Al‐4V titanium alloy and human peripheral blood mononuclear cells

Abstract: The Ti-6Al-4V titanium alloy is widely employed as an implant material. The effects of Ti-6Al-4V samples, tested in both an untreated state and one in which the samples were subjected to a glow-discharge treatment performed with the use of air, on human peripheral blood mononuclear cells (PBMC) were studied. Apoptosis, undetectable after 24-h contact of PBMC with the two sample types, is induced after 48 h by treated samples, and, after 48 h, but in the presence of 1.5 microg/mL PHA, by both sample types. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
(36 reference statements)
0
15
2
Order By: Relevance
“…It was suggested that Ni 2+ and Co 2+ -induced CAM expression could be a result from metal ion attachment to proteins presented to the cultured ECs [20], due to the involvement of oxygen radicals [18,82], or due to the inhibition of the biological activity of nitric oxide [82]. More recent studies focused on the culture of ECs with bulk permanent implant materials and reported: no significant CAM expression after culture with NiTi, CoCrNi, or NiCr [21]; significant ICAM-1 and VCAM-1 expression induced by the ion release from Ti-6Al-4V alloy [22]; and significant E-selectin expression induced by the ion release from NiTi wires [23]. …”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that Ni 2+ and Co 2+ -induced CAM expression could be a result from metal ion attachment to proteins presented to the cultured ECs [20], due to the involvement of oxygen radicals [18,82], or due to the inhibition of the biological activity of nitric oxide [82]. More recent studies focused on the culture of ECs with bulk permanent implant materials and reported: no significant CAM expression after culture with NiTi, CoCrNi, or NiCr [21]; significant ICAM-1 and VCAM-1 expression induced by the ion release from Ti-6Al-4V alloy [22]; and significant E-selectin expression induced by the ion release from NiTi wires [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Petri dishes (℘ 60 mm) with HUVEC cocultured with PBMC stimulated with 1.5 μg/mL PHA were used as controls. At the end of the coculture incubation time, PBMC were removed by vigorous washing with cold PBS and the detachment of monocytes was controlled by phase‐contrast microscopy, as previously reported 33. Then HUVEC were collected for the determination of ICAM‐1, VCAM‐1, and E‐selectin by Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The optical density was determined in an ELISA reader using a 405 and 490 nm (reference) filters. Poly(ADP‐ribose)polymerase (PARP) was determined as previously reported 32, 33…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous researches we have tested the biocompatibility of surface‐treated Ti‐6Al‐4V titanium alloy and surface treated AISI 316L austenitic stainless steel, using as experimental model both Human Umbilical Vein Endothelial Cells (HUVEC) and Human Peripheral Blood Mononuclear Cells (PBMC) 35–37. The choice of HUVEC and PBMC cultures for verifying biocompatibility was justified by these considerations.…”
Section: Introductionmentioning
confidence: 99%